Enthalpy relaxation studies in polymethyl methacrylate networks with different crosslinking degrees - Alves, N. M. (2005)
Structural relaxation of PMMA networks with distinct crosslink density has been studied by differential scanning calorimetry (DSC). The crosslinking agent used was ethylene glycol dimethacrylate (EGDMA). The experiments were carried out on heating after the samples have been subjected to distinct thermal histories, namely isothermal stages at different temperatures below the glass transition temperature for distinct times and cooling at different rates. These studies revealed a broadening of the glass transition with increasing crosslinking degree due to the constraints imposed by the crosslinks and suggested the presence of crosslink heterogeneity in the networks. A phenomenological model based on the configurational entropy concept was used to simulate the structural relaxation phenomenon and to evaluate the temperature dependence and distribution of the relaxation times of the conformational rearrangements for these networks. The agreement between the experimental results and the simulated thermograms was quite satisfactory. In addition, the kinetic fragility of the networks was evaluated from the results corresponding to the thermal treatments at distinct cooling rates. It was found an increase of the fragility index m with increasing crosslinking degree.